'Creative blocs': action research study on the implementation of Lego as a tool for reflective practice with social care practitioners. Issue 2 (4th March 2017) - Cavaliero, Tamsin
Abstract : The aim of this study is to investigate whether Lego could be used as a tool for reflective practice with social care practitioners (SCPs) and student practitioners. This article outlines an action research study conducted in an institute of higher education in Ireland. Findings from this study suggest that Lego can be used to support student practitioners struggling to make connections between theory and practice and facilitate expression of tacit understandings that can shape practice in welfare services and care environments. Furthermore, the use of Lego provides practitioners with accessible ways of communicating when attempting to engage diverse audiences with students and practitioners in social care settings.